2022
DOI: 10.3390/jof8030259
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Indigenous Candida oleophila and Candida boidinii in Monoculture and Sequential Fermentations: Impact on Ethanol Reduction and Chemical Profile in Chilean Sauvignon Blanc Wines

Abstract: The study of non-Saccharomyces yeasts in wine fermentations allows the exploration of new alternatives for the reduction of ethanol in wines. The objective of this work was to evaluate the fermentation capacity of two indigenous Candida yeasts (C. oleophila and C. boidinii) in monoculture and sequential fermentations (laboratory and microvinification scale) to produce Chilean Sauvignon Blanc wine. Fermentations were monitored by the determination of ethanol, glycerol, organic acids, and residual sugars. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Non-Saccharomyces yeasts, particularly Candida oleophila and Candida boidinii, have gained little attention in enological research, unlike other commercial strains including Torulaspora delbrueckii, Metschnikowia pulcherrima, and Lachancea Thermotolerans [16][17][18][19][20][21][22][23][24]. Actually, only one study reported on the fermentative potential of C. oleophila and C. boidinii and their capacity to reduce ethanol during Sauvignon Blanc wine production [33]. However, its antimicrobial qualities have not yet been studied in wine fermentation, despite the potential demonstrated in other food production areas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Non-Saccharomyces yeasts, particularly Candida oleophila and Candida boidinii, have gained little attention in enological research, unlike other commercial strains including Torulaspora delbrueckii, Metschnikowia pulcherrima, and Lachancea Thermotolerans [16][17][18][19][20][21][22][23][24]. Actually, only one study reported on the fermentative potential of C. oleophila and C. boidinii and their capacity to reduce ethanol during Sauvignon Blanc wine production [33]. However, its antimicrobial qualities have not yet been studied in wine fermentation, despite the potential demonstrated in other food production areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, this may be due to the aforementioned lack of control over LAB (Table 2), given that the presence of hetero-fermentative LAB can increase CO 2 and ethanol concentrations in wine [40]. The rapid fermentation caused by C. boidinii yeast compared with C. oleophila had already been reported in the literature [33], where sequential fermentation with the yeasts C. boidinii-S. cerevisiae finished fermentation by day 8, while the C. oleophila-S. cerevisiae duo finished by day 15. The importance of this lies in the fact that ethanol is considered an active bio-controlling compound [15] since most microorganisms are inhibited by high concentrations of this compound.…”
Section: Candida Spp Yeasts Produce Antimicrobial Effects In Grape Mustmentioning
confidence: 95%
See 2 more Smart Citations